Multiplatform application development with for HTML5 smartphones - Petroff, Marcelo (2012)
This paper presents an architecture for the development of software for smartphones. It explains the advantages of web application development with respect to native applications - those installed on mobile devices that were developed using a programming language compatible with the operating system used by the device. It also describes frameworks and software development kits currently available under the free software paradigm. Alternatives are presented for developing the user interface with support for HTML5 and cloud computing through which we can expose the data service and application. It explains the contributions of HTML5 for mobile applications and platforms that currently Android, iPhone OS and BlackBerry - as a distinguished group based on the number of devices and network traffic.